catena-Poly[[[bis(4-methylbenzoato-κ(2) O,O′)zinc(II)]-μ-4,4′-bipyridine-κ(2) N:N′] tetrahydrate] - Li, Xiao-Yan (International Union of Crystallography, 2009)
The asymmetric unit of the title compound, {[Zn(C(7)H(7)O(2))(2)(C(10)H(8)N(2))]·4H(2)O}(n), contains a highly distorted octahedral Zn(II) metal center strongly coordinated by two N atoms of two 4,4′-bipyridine (4,4′-bipy) ligands and chelated by two 4-methylbenzoate anions. The crystallographic inversion center and glide plane present at the center of the C—C single bond of 4,4′-bipy, along with the cis coordination motif of the 4,4′-bipy, lead to one-dimensional zigzag chains. There are a large number of water molecules in the crystal structure, which also form one-dimensional chains through O—H⋯O hydrogen bonds.